Decadal diatom oxygen isotope record of the Mid-Holocene (ca. 6.140-6.347 cal. ka BP) of the sediment core segment EN20001_6 from Lake Khamra, Yakutia, Siberia - Amelie Stieg; Mikaela Weiner; Andreas Marent; Boris K Biskaborn; Ulrike Herzschuh; Izabella Baisheva; Luidmila A Pestryakova; Hanno Meyer (PANGAEA, 2025)
The dataset compiles diatom oxygen isotope data of 22 samples from the sediment core segment EN20001_6, Lake Khamra. The record has a decadal resolution and spans approximately 210 years (6.140-6.347 cal. ka BP, mean ages) within the Mid-Holocene. Contamination assessment, conducted on purified lake sediment samples, was performed by Energy-Dispersive X-ray Spectroscopy (EDS) measurements, carried out by a JEOL M-IT500HR analytical scanning electron microscope (SEM) with an integrated EDS-system supplied with a Peltier-element-cooled detector (SDD) at AWI Potsdam. The standardless procedure was used according to Chapligin et al. (2012), performing six repetitions with an acceleration voltage of 20.0 kV, magnification of 300 and a measuring time of 30 seconds. All detectable elements are given as oxides, with weight percentages (in %) and summed up to the total sum (total %) of each sample. The diatom oxygen isotope data was generated in the ISOLAB Facility at AWI Potsdam with a semi-automated laserfluorination line (Chapligin et al., 2010) in combination with a SERCON HS2022 mass spectrometer. All δ18Odiatom values are given in per mill ( extperthousand) vs. Vienna Standard Mean Ocean Water (VSMOW). The dataset includes the mean of measured δ18Odiatom values (Diatom δ18O mean), its standard deviation (Diatom δ18O std dev) and number of replicates (Repl), as well as the calculated contamination (Contamination in %) and the δ18Odiatom corrected for contamination (Diatom δ18O corr). Details of the contamination correction and isotope analytics are given in Stieg et al. (in process).